Strategy to Improve Service Quality Using Importance Performance Analysis Method in the Outpatient Unit of Balikpapan Baru Hospital, East Kalimantan - Noviana Indarti; Endang Komara; Ign Wiseto P Agung (Research of Service Administration Health and Sains Healthys, 2025)
A hospital is one of the health service facilities that provides individual health services in a complete manner. Hospital services include inpatient, outpatient and emergency services. In reality, often hospital services to their patients are often still of poor quality in various dimensions, be it tangible, reliability, emphaty, safety and responsiveness. So this causes dissatisfaction for patients, because there is a gap between expectations and reality obtained. In the health sector, patients can provide value based on the satisfaction of the services they receive so that it can be an evaluation for service providers to be able to improve or maintain the quality of their services. The level of patient satisfaction then becomes a benchmark in the success rate of a health service. The purpose of this study is to develop a strategy to improve the quality of hospital services in the Outpatient Unit of Balikpapan Baru Hospital, East Kalimantan by analyzing patient satisfaction using the Importance Performance Analysis method. The study population is patients who come to the Outpatient Unit of the Midwifery Clinic, with a sample of 55 people. The research instrument was in the form of a questionnaire. Based on the results of the study, it shows two dimensions of service that must be prioritized, namely the dimensions of responsiveness and emphaty. Meanwhile, the services that must be maintained in performance are the dimensions of reliability and safety.